Memories of early caregiver eating messages and binge eating symptomatology in Portuguese adults: The role of body appreciation - Oliveira, Sara (2018)
Objectives: The current study aimed to explore the relationship between memories of caregiver eating messages and binge eating symptomatology, and to test whether body appreciation mediates this association. Method: A total of 246 women and 133 men from the general population, aged between 18 and 60, participated in this study, by completing online self-report instruments to evaluate memories of early caregiver eating messages, body appreciation, and binge eating symptomatology. Results: Results revealed negative associations between memories of early caregiver eating messages and body appreciation, and negative associations between body appreciation and binge eating symptomatology. Results indicated that body appreciation acts as a mediator in the relationship between caregiver restrictive and critical eating messages and binge eating symptomatology, while pressure to eat messages did not present significant associations. Specifically, individuals who recall more restrictive and critical eating messages, show higher levels of binge eating symptomatology, via lower levels of body appreciation. The tested model explained 35% in the variance of binge eating symptomatology and did not reveal significant differences between females and males. Conclusions: This study seems to support that parental control of children feeding is related to a low tendency to adopt a positive relationship with body image and with a higher probability to engage in disordered eating behaviors, such as binge eating symptomatology. Therefore, these findings highlighted the importance of developing parental methodologies focused on the development of adaptive strategies to regulate their children's eating behaviors that allow the event of an appreciative body image.